Observation of Pattern Stabilization in a Driven Superfluid - Nikolas Liebster; Marius Sparn; Elinor Kath; Jelte Duchene; Keisuke Fujii; Sarah L. Görlitz; Tilman Enss; Helmut Strobel; Markus K. Oberthaler (Physical Review X)
The formation of patterns in driven systems has been studied extensively, and their emergence can be connected to a fine balance of instabilities and stabilization mechanisms. While the early phase of pattern formation can be understood on the basis of linear stability analyses, the longtime dynamics can only be described by accounting for the interactions between the excitations generated by the drive. Here, we observe the stabilization of square patterns in an interaction-driven, two-dimensional Bose-Einstein condensate. These patterns emerge due to inherent high-order processes that become relevant in the regime of large phonon occupations. Theoretically, this can be understood as the emergence of a stable fixed point of coupled nonlinear amplitude equations, which include phonon-phonon interactions. We experimentally probe the predicted flows toward such a stable fixed point, as well as repulsion from a saddle fixed point, using the experimental control unique to quantum gases.